Pilgrim Law - Rodes, Robert E. (Journal of law and religion, 1994)
A people's laws are deeply imbedded in its culture. They embody its collective moral reflection, its common understanding of the terms on which human beings are to live together, its customs, its historical experience, and its aspirations for the future. It is perhaps to be expected that Americans should enshrine their constitutional documents, build courthouses like temples, deploy their laws with ruthless practicality, and not take kindly to the suggestion that their laws are less practical than they think. Or that Italians should maintain a legal system like an old palazzo, with imposing staircases you can lose your breath climbing, bizarre opening hours, a wing or two closed for restoration, and a few kindly people who will sometimes show you where the elevator or the back door is hidden.It is the cultural range of the subject matter that makes the study of jurisprudence interesting. There are philosophies of law, some good, some bad, some indifferent, but philosophy does not exhaust the subject of jurisprudence, because major jurisprudential questions (for example, what is a corporation) are not philosophical. There are theologies of law also, but they do not exhaust the subject either. As Christopher St. Germain had a sixteenth century theologian point out to a law student, the law of God is not concerned with land titles. Granted, it would be possible to distribute land titles in such a way as to offend the law of God, but the point stands nevertheless. It would also be possible to build a theologically unacceptable house (say a firetrap), but that does not make architecture a branch of theology.